2021
DOI: 10.1111/are.15262
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, fillet quality and immunity after challenge with streptococcus agalactiae of red tilapia ( oreochromis sp .) fed diet containing cysteamine and creatine

Abstract: This study aimed to evaluate the effect of creatine and cysteamine supplementation on the growth performance, fillet quality and resistance to bacterial infection of Streptococcus agalactiae in red tilapia. Five types of experimental diet (quadruplicate) with the same energy and protein content were tested. These consist of N (negative control), A (0.5 g/kg cysteamine), B (0.4 g/kg creatine), C (0.5 g/kg cysteamine plus 0.4 g/kg creatine) and D (0.25 g/kg cysteamine plus 0.2 g/kg creatine). Male red tilapia (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…GPx, via the reduced glutathione (GSH) pathway, can reduce hydrogen peroxide and fatty acid hydroperoxides in the cytosol and mitochondria to water and alcohol [ 18 , 44 ]. Selenium can also increase the number of SOD enzymes in the animal body by reducing the amount of superoxide anion if the amount is excessive due to oxidative stress [ 7 , 8 , 36 , 45 ]. The amount of ROS that is not excessive plays a critical role in the signalling process of many cells, whereas an excessive amount can damage important biological molecules of the body, including nucleic acids, proteins, and lipids [ 9 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GPx, via the reduced glutathione (GSH) pathway, can reduce hydrogen peroxide and fatty acid hydroperoxides in the cytosol and mitochondria to water and alcohol [ 18 , 44 ]. Selenium can also increase the number of SOD enzymes in the animal body by reducing the amount of superoxide anion if the amount is excessive due to oxidative stress [ 7 , 8 , 36 , 45 ]. The amount of ROS that is not excessive plays a critical role in the signalling process of many cells, whereas an excessive amount can damage important biological molecules of the body, including nucleic acids, proteins, and lipids [ 9 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, Wang et al [ 47 ] reported that THC and AL of juvenile Chinese mitten crab Eriocheir sinensis decreased under nitrite stress at 2 mg L −1 but increased with increasing selenium doses (0.5–1 mg Se kg feed −1 ). Lysozyme is one of the key defense components against pathogens and oxidative stress due to the lack of an adaptive immune system in crustaceans [ 62 ] and fish [ 7 , 8 ]. Lysozyme activity is a crucial indicator of innate immunity because it can act as antibacterial, antiviral, and anti-inflammatory [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…119,120 Creatine along with carbohydrates improves muscle creatine retention compared to creatine alone. 72 Furthermore, creatine stimulates insulin secretion, 29,127 increases muscle glycogen stores (see above) and ameliorates hyperglycaemia. In addition, exercise induces numerous metabolic benefits, including insulin-independent muscle glucose uptake and insulin sensitivity.…”
Section: Carbohydrate Utilisationmentioning
confidence: 99%
“…CSH has been supplemented in cell media for mammalian oocyte maturation (39), but the effects of CSH on muscle cells is still unknown. CSH has been proposed as a growth promoter additive in animal nutrition, including sheep, chicken, yak and pig (38,40,41) and recently, also in different fish species, such as in red tilapia (Oreochromis niloticus), orange-spotted grouper (Epinephelus coioides) and common carp (Cyprinus carpio) (42)(43)(44). However, there is not a consensus about the underlying mechanisms and the optimal inclusion dose, due to its association with several negative effects on growth, hormonal regulation, oxidative stress and welfare (27,(44)(45)(46).…”
Section: Introductionmentioning
confidence: 99%